Anaerobic biorefinery: Current status, challenges, and opportunities. (September 2016) - Sawatdeenarunat, Chayanon; Nguyen, Duc; Surendra, K.C.; Shrestha, Shilva; Rajendran, Karthik; Oechsner, Hans; Xie, Li; Khanal, Samir Kumar
Highlights: Anaerobic biorefineries are a new approach for producing biobased products. Most organic substrates can be used as feedstocks for anaerobic biorefineries. Large-scale biorefineries have the potential to maximize economic benefit. Small-scale anaerobic biorefineries improves living quality in developing countries. Abstract: Anaerobic digestion (AD) has been in use for many decades. To date, it has been primarily aimed at treating organic wastes, mainly manures and wastewater sludge, and industrial wastewaters. However, with the current advancements, a more open mind is required to look beyond these somewhat restricted original applications of AD. Biorefineries are such concepts, where multiple products including chemicals, fuels, polymers etc. are produced from organic feedstocks. The anaerobic biorefinery concept is now gaining increased attention, utilizing AD as the final disposal step. This review aims at evaluating the potential significance of anaerobic biorefineries, including types of feedstocks, uses for the produced energy, as well as sustainable applications of the generated residual digestate. A comprehensive analysis of various types of anaerobic biorefineries has been developed, including both large-scale and household level applications. Finally, future directives are highlighted showing how anaerobic biorefinery concept could impact the bioeconomy in the near future.